Perbandingan latihan resistance dan ladder untuk meningkatkan kecepatan lari pemain futsal SMA N 3 Pemalang - Liyalin Mubarok (YLPK Mahardhika, 2021)
This research is motivated by the physical condition of the running speed of the extracurricular futsal team of SMA Negeri 3 Pemalang which is not good, this can be seen from the many players who do not have a maximum running speed. This study aims to determine the effect of the resistance band and ladder exercises in increasing running speed in futsal games and to find out which exercises are more effective. The research subjects sampled in the study were 16 students of SMA N 3 Pemalang who participated in futsal extracurricular activities which were divided into 2 groups, namely the first group of 8 resistance band exercises and the second group of 8 ladder exercises. Data collection was carried out with a 60-meter running speed test on the Cibelok soccer field. The research design used was a pre-test and post-test group, therefore, data collection was carriedout during the pretest and posttest. Based on the calculation results, it was found that the increase in running speed with Resistance band training was 4.95%, while with Ladder training it was 13.58%. So that Ladder training is more effective to increase running speed. The conclusion of this study is that the Ladder training method is more effective and good in increasing the running speed of futsal extracurricular players at SMAN 3 Pemalang.